Rational Design of Single Atomic Co in CoNx Moieties on Graphene Matrix as an Ultra‐Highly Efficient Active Site for Oxygen Reduction Reaction. Issue 2 (21st January 2020) - Shu, Yasuhiro; Miyake, Koji; Quílez‐Bermejo, Javier; Zhu, Yexin; Hirota, Yuichiro; Uchida, Yoshiaki; Tanaka, Shunsuke; Morallón, Emilia; Cazorla‐Amorós, Diego; Kong, Chang Yi; Nishiyama, Norikazu
Abstract: The sharp increase in current energy consumption needs the development of fuel cells (FCs) as one of sustainable, renewable, efficient and eco‐friendly electrochemical conversion systems of energy. The performance of electrocatalysts is crucially important for commercialization of FCs. Commercial Pt based catalysts are used due to their high catalytic activity. However, widespread commercialization is impossible because of the scarcity and poor durability of Pt based catalysts. We are on our quest to find a more stable and affordable alternative catalyst of Pt based catalysts. In particular, single‐atom catalysts supported on graphene are greatly attractive because of their unique characteristic and high catalytic activity. In this work, graphene is hydrothermally treated by sulfuric acid to introduce the ion‐exchanging sites. Then, Co 2+ ion‐exchanging, 2‐methylimidazole coordination and pyrolysis process are subsequently conducted to prepare highly‐dispersed single‐atom Co species catalyst with outstanding ORR activity and durability. This work presents a new direction for a rational design of single‐atom catalyst on carbon matrix. Abstract : A new direction for a rational design of single‐atom catalyst on carbon matrix was presented hererin. The single atomic Co is designed in CoNx moieties on graphene matrix, which acts as an ultra‐highly efficient active site for oxygen reduction reaction.